Bridging or Deepening the Digital Divide: Influence of Household Internet Access on Formal and Informal Volunteering. (April 2019) - Piatak, Jaclyn; Dietz, Nathan; McKeever, Brice
The digital divide persists; a quarter of the U.S. population is unconnected, left without Internet access at home. Yet volunteer recruitment is increasingly moving online to reach a broader audience. Despite widespread use, little is known about whether the lack of digital access has repercussions on connections offline in the community. We examine the influence of access on volunteering across four critical aspects—structure, time devoted, level of professionalization, and pathways to volunteering. We find home Internet access has an independent influence on volunteering even after controlling for socioeconomic status. Those with access are more likely to volunteer, formally and informally, and are more likely to become volunteers because they were asked. However, digitally unconnected volunteers devote more time. Nonprofit organizations and government agencies should be strategic and inclusive in their volunteer recruitment efforts to ensure they recruit qualified and dedicated volunteers rather than rely solely on digital recruitment strategies.